Analysis of coding DNA sequence of GDF9 gene in Indian goats for prolificacy associated markers - Ahlawat, Sonika; Sharma, Rekha; Maitra, A (The Indian Journal of Animal Sciences, 2012)
The present study was undertaken to characterize complete coding DNA sequence of one of fecundity genes: GDF9 (Growth differentiation factor 9), in a panel of 6 breeds of indigenous goats with different prolificacy. Nine nucleotide differences were identified between sheep (AF078545) and goats in exon 1 and flanking region and 9 transitions were seen in exon 2. Three non-synonymous SNPs (C818T, A959C and G1189A) were detected in exon 2 of indigenous goat breeds. One of the SNPs (A959C) identified in present study has been associated with high prolificacy in exotic goats. These SNPs were different from the 4 mutations (FecGH, FecGE, FecTT and G1) associated with fecundity in sheep. GDF9 coding DNA sequence of Indian goat was 99% similar to exotic goat as well as sheep, whereas it depicted 97% homology with Bos taurus. In silico translation of obtained coding DNA sequence of GDF9 gene in indigenous goats revealed a sequence of 454 amino acids with 1 change between Indian goat and exotic goat, 5 amino acid changes between Indian goat and sheep and 21 changes between Indian goat and cattle.